Islamic Education Teachers Strategies for Character Building Through Digital Literacy Based Islamic Values in The Society 5.0 Era - Nasution, Henni Syafriana; Basri, Hasan; Batubara, Winda Wasalwa; Mukhlasin, Ahmad (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
This study examines the challenges faced by Islamic Education teachers at MAN 1 Langkat, MAN 1 Deli Serdang, and MAN 1 Medan in shaping student character in the era of Society 5.0, particularly in balancing the teaching of moral values and noble character with the use of digital technology. The purpose of this study is to analyze the role of teachers as agents of change, innovative strategies in learning and assessment, and best practices for synergizing technology, curriculum, and Islamic character education. The research used a qualitative approach with a multi-site case study, involving in-depth interviews, classroom observations, and documentation studies. The results showed that Islamic education teachers act as role models, motivators, and facilitators, using digital platforms such as e-learning, blended learning, and social media for interactive learning, while instilling moderate Islamic values such as tolerance and inclusiveness. Authentic assessments through portfolios, projects, and self-assessments support holistic character evaluation. These findings confirm that strengthening teacher competencies and integrating technology, curriculum, and Islamic character education are key to shaping a smart, character-driven, and adaptive generation in a pluralistic society.